PERSEPSI MAHASISWA FISIP UNDIP TERHADAP KEBIJAKAN PENGURANGAN SUBSIDI BBM - Adi Syafutra; Priyatno H; Nunik Retno (Journal of Politic and Government Studies, 2014)
AbstractRecently there have been many student actions that occured in Indonesia as student political attitude toward social and political condition as well as policies set by the government. One of the policies that was recently refused by the students was the policy to reduce fuel subdidy. It is interesting to know that students gave a lot of attention in this matter. Most students have tried to find out about this policy, followed the process of the production of the policy, and gave their opinion about the policy. This matter has drawn a lot of attention form students because fuel itself is one of society basic needs. Therefore, from this fact, the writer was interested to find out more about student perception towards the government policy to reduce the fuel subdidy in reality.Based on the result of the research, according to students from Faculty of Social and Politics majoring in govenrment, the government had done the right thing by cutting the budget for fuel subsidy through reducing fuel subsidy. They considered that fuel subsidy itself was not really gave the benefit for medium low class society and it was also not exactly benefited the medium low society instead it was the medium high class society who was benefited for this. However, still according to them, the government had also made mistake with this policy to reduce fuel subdidy because this policy was not followed by a good plan to overcome the impact that it had caused that finally ended up with bad impact for middle low society.Keywords: Policy to reduce fuel subsidy, Student Perception